2017
DOI: 10.1098/rsob.160328
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of disrupted-in-schizophrenia 1 aggregates between neuronal-like cells occurs in tunnelling nanotubes and is promoted by dopamine

Abstract: The disrupted-in-schizophrenia 1 (DISC1) gene was identified as a genetic risk factor for chronic mental illnesses (CMI) such as schizophrenia, bipolar disorder and severe recurrent depression. Insoluble aggregated DISC1 variants were found in the cingular cortex of sporadic, i.e. non-genetic, CMI patients. This suggests protein pathology as a novel, additional pathogenic mechanism, further corroborated in a recent transgenic rat model presenting DISC1 aggregates. Since the potential role of aggregation of DIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
(137 reference statements)
1
10
0
Order By: Relevance
“…In fact, insoluble aggregates of disrupted‐in‐schizophrenia 1 (DISC1) were associated to sporadic cases of schizophrenia, bipolar disorder, and depression (Korth, 2012; Leliveld et al, 2008). In addition, in vitro studies have demonstrated that aggregates of DISC1 are able to transfer between cells via tunneling nanotubes (Zhu, Abounit, Korth, & Zurzolo, 2017). These aggregates can selectively affect dopaminergic brain functioning at presynaptic and postsynaptic level (Dahoun, Trossbach, Brandon, Korth, & Howes, 2017; Tropea, Hardingham, Millar, & Fox, 2018), and, as they are related to oxidative stress (Trossbach et al, 2016), the transneuronal spread hypothesis is not incompatible with the metabolic stress model.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, insoluble aggregates of disrupted‐in‐schizophrenia 1 (DISC1) were associated to sporadic cases of schizophrenia, bipolar disorder, and depression (Korth, 2012; Leliveld et al, 2008). In addition, in vitro studies have demonstrated that aggregates of DISC1 are able to transfer between cells via tunneling nanotubes (Zhu, Abounit, Korth, & Zurzolo, 2017). These aggregates can selectively affect dopaminergic brain functioning at presynaptic and postsynaptic level (Dahoun, Trossbach, Brandon, Korth, & Howes, 2017; Tropea, Hardingham, Millar, & Fox, 2018), and, as they are related to oxidative stress (Trossbach et al, 2016), the transneuronal spread hypothesis is not incompatible with the metabolic stress model.…”
Section: Discussionmentioning
confidence: 99%
“…is optimal to study TNTs [19,125,[129][130][131]. HeLa cells WT, HeLa cells myrlysin-KO and KIF1B-KIF5B double KO [100,132], and HeLa cells stably expressing Gal3-Turquoise were cultured in DMEM-GlutaMAX including 4.5 g/L D glutamine and pyruvate (Gibco) supplemented with 10% of FBS.…”
Section: Plos Biologymentioning
confidence: 99%
“…Prions and prion-like proteins were also shown to utilize TNTs for their spreading. Specifically, TNTs were shown to transfer PrP Sc , alpha-synuclein, tau, beta-amyloid, polyglutamine huntingtin and disrupted-in-schizophrenia 1 (DISC1) aggregates [19][20][21][22][23]. Therefore, it has been proposed that by allowing prion-like protein spreading in the brain, TNTs could have a prominent role in the pathogenesis of different neurodegenerative diseases [22].…”
Section: Introductionmentioning
confidence: 99%